Integrated Guidance and Control Using Adaptive Backstepping Approach for Maneuvering Target Interception. Issue 2 (2020) - Pei, Pei; Ji, Yi; He, Shaoming; Wang, Jiang; Lin, Defu
Abstract: A novel approach to address the problem of integrated guidance and control(IGC) for a missile is studied in this paper. By taking target maneuver, aerodynamic uncertainty and fin servo dynamic uncertainty as external disturbances in the adaptive backstepping design procedure, the proposed controller requires no information on target maneuver and provides robustness against these uncertainties. Furthermore, the derivatives of the virtual control laws in the backstepping differentiation process are estimated by a smooth second-order sliding mode differentiator, this simplifies the calculation and avoids the explosion of terms phenomenon in the conventional backstepping method. The closed-loop stability of the overall system is supported by the Lyapunov stability theory. Numerical simulations of an air-to-air interception scenario are presented in the simulation part to verify the superior performance and the robustness of proposed IGC law.